How AI Chatbot works: Simplifying the Magic of Conversational AI - Hari Kiran Vuyyuru (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the fundamental mechanisms and capabilities of Generative AI, examining how this advanced language model achieves human-like conversational abilities. The article delves into the system’s core components, including its sophisticated tokenization processes, context management mechanisms, next-token prediction capabilities, and training methodologies enhanced through human feedback. Through a detailed analysis of recent research findings, the article demonstrates how Generative AI chatbot transcends simple pattern matching to achieve complex reasoning, creative generation, and adaptive communication abilities across various specialized domains. Special attention is given to the model’s applications in healthcare, education, and enterprise settings, highlighting its remarkable achievements and inherent limitations compared to human cognition.